N-doped graphdiyne for high-performance electrochemical electrodes. (February 2018) - Shang, Hong; Zuo, Zicheng; Zheng, Haiyan; Li, Kuo; Tu, Zeyi; Yi, Yuanping; Liu, Huibiao; Li, Yongjun; Li, Yuliang
Abstract: A novel method is developed for constructing well-defined N-doped graphdiyne (GDY) nanostructures. This method can effectively tune the N-configurations (pyridinic N and triazine-like N cluster), N-content, and porous structures of GDYs, indicating good controllability. The N-configurations and structure of GDYs are well confirmed by the X-ray photoelectron spectrometer measurements, nitrogen absorption measurements and neutron pair distribution function (PDF), respectively. The as-prepared GDYs can be assembled into high-performance two-electrode supercapacitors with specific capacitance high up to 250 F g −1, delivering an energy density of 8.66 Wh kg −1 and power density of 19.3 kW kg −1 ; the well-defined N-configuration in GDYs offers us an opportunity to understand the controversial nitrogen role in catalyzing the oxygen reduction reaction in sp 2 carbons. Importantly, this method for creating well-defined N-doped GDYs may widely extend the GDY materials for new energy fields. Graphical abstract: A novel method is developed for efficiently constructing well-defined N-doped graphdiyne (GDY) with microporous structure. The as-prepared GDYs have high surface area and 3D continuousness, and can be applied as promising electrodes for high-performance symmetric supercapacitors (250 F g −1 ) and metal-free catalysts of oxygen reduction reaction. Highlights: A novel method is developed for constructing well-defined N-doped graphdiyne (GDY) with microporous structure. N-configurations, N-content, and porous structures of GDYs can be effectively tuned. The GDYs can be assembled into high-performance two-electrode supercapacitors with high specific capacitance. This method for creating well-defined N-doped GDYs may extend the GDY materials for new energy fields.